Why Women Wear What They Wear? Exploring Young Adults’ Attitude towards Western Attires of Women in Bangladesh - Kazol, Sumaiya Jahan; Rana, Sohel (Indonesian Journal of Social Research (IJSR), 2025)
Bangladesh has different religious beliefs, diverse socio-economic backgrounds, and some distinct cultural practices. Diversity among people is reflected in their attitudes and behavior in every aspect of their lives, including their attire. The research aims to explore the attitude of the young adults of the capital city (Dhaka) towards the Western attires of women as well as the factors that shape their attitude in a time when women wearing Western attires are facing restrictions due to people's concerns about their social and cultural beliefs and religious identities. Primary data for this study were collected through a semi-structured questionnaire and in-depth interviews with the young adults of Dhaka. The quantitative data were analyzed using a descriptive statistical technique (percentage analysis), and the qualitative data were analyzed using thematic analysis. The findings reveal that the five key factors that shape the attitude of young adults towards the Western attires of women's factors include the various social, cultural, economic, and religious aspects, as well as the influence of modernization. Their attire choice varies based on age, gender, marital status, educational qualifications, religion, professions, and economic conditions. While women, unmarried, educated, wealthy, people working in the corporate sector, and the younger people of Dhaka are more likely to support Western attires, the Muslims, male, married, and the respondents of older age groups oppose provocative dresses. They emphasize social, cultural, and religious norms and maintain decency in overcoming dress-related disputes in Bangladesh.